Retreatment of Chronic HCV Infection after Second Generation DAA Failure in Patients in the NJ VA Healthcare System. (4th October 2017) - Stawarz, Kimberly; Kaminski, Clinton; Kaminski, Sandra; Sonyey, Alexandra
Abstract: Background: The data on retreatment of patients with second-generation DAA treatment failure is limited. AASLD retreatment guidelines were established but are classified as class IIb/Level C. We analyzed treatment outcomes in NJ VA patients with prior second-generation DAA failure over a period of 1 year. Methods: We performed a retrospective health record review of all HCV patients treated between May 1, 2016 and May 1, 2017. HCV genotypes (GT), the presence of cirrhosis and HIV, DAA type, and RAVs post treatment were evaluated in the treatment failure (TF) group, defined as an inability to achieve the sustained virological response 12 weeks post therapy (SVR12). These patients were retreated with a new DAA regimen selected for their individual characteristics, GT and presence of RAVs and retreatment success rates were recorded. Results: Of 312 HCV patients, 10 failed second-generation DAA therapy during the outlined period. The TF group had 2 patients with HIV, 5 with cirrhosis, 6 with GT 1a, 2 with GT 1b, and 2 with GT 3a. Patients with GT 1a/b were initially treated with Ledipasvir/Sofosbuvir (LDV/SOF) ± Ribavirin (RBV). One patient with GT 3a was treated with LDV/SOF +RBV, and 1 with SOF+RBV. Three patients stopped treatment early due to side effects or non-compliance. Post-treatment resistance panel was available for 7/10 patients with the following detected mutations: Q30H/K/E/R, L31 L/M, Q20Q, M28V, Q80K, Y93A/H. 2/8 GT1a/b patients were re-treated with SOF/Elbasvir(EBR)/Grazoprevir(GZR)/RBV, 2 with SOF/ Velpatasvir (VEL)/RBV, 2 with EBR/GZR+/-RBV, and 2 with Viekira/SOF/RBV. 1 patient with GT 3a was retreated with SOF/Daclatasvir (DAC), 1 with SOF/VEL/RBV. All 10 patients had an undetectable viral load (VL) at the end of treatment. SVR12 has been achieved for all 5 patients that were tested, with the remaining 5 awaiting week 12. Conclusion: The HCV second-generation DAA treatment failure rate in patients at the NJ VAHCS over 1 year was 3.2%. Analysis of available data indicates that the presence of RAVs might be the major cause of treatment failure among HCV patients treated with DAAs in NJ VA. Different retreatment regimens were used for a period of 12–24 weeks with 100% undetectable VL at end of treatment. Disclosures: All authors: No reported disclosures.